An Overview of B-1 Cells as Antigen-Presenting Cells - Popi, Ana F.; Longo-Maugéri, Ieda M.; Mariano, Mario (Frontiers in Immunology, 2016)
The role of B cells as antigen-presenting cells has been extensively studied, mainly in relation to the activation of memory T cells. Considering the B cell subtypes, the role of B-1 cells as antigen-presenting cells is beginning to be explored. Initially, it was described that B-1 cells are activated preferentially by T-independent antigens. However, some reports demonstrated that these cells are also involved in a T-dependent response. The aim of this review is to summarize information about the ability of B-1 cells to play a role as APCs and to briefly discuss the role of the BCR and TLR signals in this process. Furthermore, some characteristics of B-1 cells, such as natural IgM production and phagocytic ability, could interfere in the participation of these cells in the onset of an adaptive response.